2017
DOI: 10.1177/1179556517709021
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Neonatal Transport in Western Switzerland: A Model of Perinatal Regionalization

Abstract: Neonatal transport is an essential part of regionalization for highly specialized neonatal intensive care. This retrospective analysis of prospectively collected data on neonatal transport activity in a large Swiss perinatal network more than 1 year, aimed to quantify this activity, to identify the needs for staff, and the demands regarding know-how and equipment. Of the 565 admissions to the tertiary neonatology clinic, 176 (31.2%) were outborn patients, transported as emergencies to the level III unit. In 71… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
14
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 20 publications
3
14
1
2
Order By: Relevance
“…Indication for referral were mainly prematurity (85%), respiratory distress (62%) and in 11% neonatal infection. The high rate of respiratory distress corresponds to data presented by McEvoy et al in Western Switzerland (34). However, whereas in Switzerland respiratory support is guaranteed during transportation in a fully equipped and medicalized ambulance, professional neonatal transport does not exist in Conakry.…”
Section: Neonatal Transportsupporting
confidence: 82%
“…Indication for referral were mainly prematurity (85%), respiratory distress (62%) and in 11% neonatal infection. The high rate of respiratory distress corresponds to data presented by McEvoy et al in Western Switzerland (34). However, whereas in Switzerland respiratory support is guaranteed during transportation in a fully equipped and medicalized ambulance, professional neonatal transport does not exist in Conakry.…”
Section: Neonatal Transportsupporting
confidence: 82%
“…1 The guidelines for the regionalization of perinatal care were established in order to identify high-risk pregnancies early so that both mother and baby could reach a hospital providing the appropriate level of care. 2 Previous research has shown that mortality and morbidity are higher in outborn infants compared with their inborn counterparts. 3,4 The transport environment exposes infants to known physiological stressors, and infants requiring transport are already in a compromised state.…”
mentioning
confidence: 99%
“…Um bom conhecimento geral sobre cuidado neonatal e um elevado nível de especialização em habilidades processuais são pré-requisitos para os que efetuam transferências neonatais (3) .…”
Section: Discussionunclassified
“…O transporte neonatal representa uma parte essencial de pacotes de cuidados requeridos pelos serviços perinatais (3) .…”
Section: Introductionunclassified